Antiretroviral Therapy for HIV-2 Infection in Non-Endemic Regions. - de Mendoza, Carmen; Lozano, Ana B.; Caballero, Estrella; Cabezas, Teresa; Ramos, José M.; Soriano, Vicente (AIDS Reviews)
Human immunodeficiency virus type 2 (HIV-2) was isolated in AIDS patients in 1986. Around 1-2 million people are infected worldwide. The virus is less transmissible than HIV-1, being sexual contacts the most frequent route of acquisition. In the absence of antiretroviral therapy, most HIV-2 carriers will develop AIDS; however, it takes longer than in HIV-1 infection. There is no global pandemic caused by HIV-2, as the virus is largely confined to West Africa. Due to historical ties, HIV-2 is also prevalent in Portugal and its former colonies in Brazil, India, Mozambique, and Angola. Other European countries with hundreds to thousands of HIV-2 infections are France, Belgium, and Spain. A few hundred have been reported in North America, mostly in West African foreigners. Globally, HIV-2 infections are steadily declining. Although CD4 declines occur more slowly in HIV-2 than in HIV-1 patients, the CD4 recovery with antiretroviral treatment is smaller in the former. HIV-2 is naturally resistant to non-nucleoside reverse transcriptase inhibitors (NNRTIs) and some protease inhibitors. In contrast, HIV-2 is susceptible to all NRTIs and integrase inhibitors. Drug resistance in HIV-2 may develop earlier than in HIV-1 and select for mutations at distinct sites. Misdiagnosis of HIV-2 in patients wrongly considered as HIV-1 positive or in those dually infected may result in treatment failures with undetectable HIV-1RNA. Given the relatively large number of West Africans migrated to the European Union and North America, HIV-2 infection either alone or as coinfection with HIV-1 should be excluded at least once in all HIV-seroreactive persons. This should be stressed in the face of atypical HIV serological profiles, immunovirological disconnect (CD4 cell count loss despite undetectable HIV-1 viremia), and/or high epidemiological risks (birth in or sex partners from HIV-2 endemic regions). Superinfection with any HIV variant may occur in persons infected with the other, since there is no cross-protection. Thus, earlier antiretroviral therapy is warranted for either HIV-1 or HIV-2, given that it would protect from each other superinfection in persons at risk.